2020
DOI: 10.3390/antiox10010021
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria, Oxidative Stress, cAMP Signalling and Apoptosis: A Crossroads in Lymphocytes of Multiple Sclerosis, a Possible Role of Nutraceutics

Abstract: Multiple sclerosis (MS) is a complex inflammatory and neurodegenerative chronic disease that involves the immune and central nervous systems (CNS). The pathogenesis involves the loss of blood–brain barrier integrity, resulting in the invasion of lymphocytes into the CNS with consequent tissue damage. The MS etiology is probably a combination of immunological, genetic, and environmental factors. It has been proposed that T lymphocytes have a main role in the onset and propagation of MS, leading to the inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 191 publications
(149 reference statements)
0
17
0
Order By: Relevance
“…In general, accumulating studies have proven that microglia show an anti-inflammatory phenotype and protect MNs at the onset of the disease, while end-stage microglia shift to a proinflammatory phenotype and aggravate the neurodegeneration of MNs in ALS ( Liu et al, 2021 ; Masrori et al, 2022 ). Astrocytes are the most common glial cells in the brain, maintain the CNS barriers ( Signorile et al, 2021 ), secrete neurotrophic and neuroprotective factors, regulate neurotransmitter uptake and recycling, and promote neurogenesis ( Gharbi et al, 2020 ). Studies have identified a role for astrocytes as immune modulators, as they may control the activation, migration, and proliferation of microglia ( Sunnemark et al, 2005 ; Ouali et al, 2018 ).…”
Section: Major Changes Of Resident Immune Cells In Amyotrophic Latera...mentioning
confidence: 99%
“…In general, accumulating studies have proven that microglia show an anti-inflammatory phenotype and protect MNs at the onset of the disease, while end-stage microglia shift to a proinflammatory phenotype and aggravate the neurodegeneration of MNs in ALS ( Liu et al, 2021 ; Masrori et al, 2022 ). Astrocytes are the most common glial cells in the brain, maintain the CNS barriers ( Signorile et al, 2021 ), secrete neurotrophic and neuroprotective factors, regulate neurotransmitter uptake and recycling, and promote neurogenesis ( Gharbi et al, 2020 ). Studies have identified a role for astrocytes as immune modulators, as they may control the activation, migration, and proliferation of microglia ( Sunnemark et al, 2005 ; Ouali et al, 2018 ).…”
Section: Major Changes Of Resident Immune Cells In Amyotrophic Latera...mentioning
confidence: 99%
“…Another important pathway where metabolites and genes converge is the cAMP signaling pathway. Mitochondrial stress, oxidative stress, and the cAMP signaling pathway nexus [ 50 ] appear to be correlated in heat-stressed granulosa cells [ 3 , 4 ]. Furthermore, the cAMP signaling pathway activates complex signaling involving the MAPK pathway, which can ultimately promote DNA damage and cell senescence [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, apoptosis can be triggered by a variety of stimuli including inflammatory cytokines and ROS. ROS has been extensively implicated in T cell hyporesponsiveness, apoptosis, and activation [ 24 , 25 ]. To validate this hypothesis, the levels of ROS and SOD were measured to assess the degree of oxidative stress in the spleen of PICS mice.…”
Section: Discussionmentioning
confidence: 99%